Environmental tax, carbon emmission and female economic inclusion - Michael Gift Soku; Mohammed Amidu; Coffie William (Cogent Business & Management, 2023)
This research examines the nexus between environmental tax, carbon emission, and female economic inclusion. The study employs a quantitative research method, utilizing the Generalized method of moments (GMM) on a dataset of 65 countries from the period 1994 to 2020. The research finds that environmental tax has a significant negative effect on carbon emission, and that firms with a higher level of female economic inclusion tend to have lower carbon emission levels. Furthermore, the research shows that firms with a higher level of female economic inclusion are more likely to implement environmentally sustainable practices, which in turn reduces their carbon emission levels. These findings suggest that policies that promote environmental taxation and female economic inclusion can be effective in reducing carbon emissions and promoting sustainable business practices. The sampling technique used in this study is purposive sampling, where 64 countries were selected based on their availability of data on environmental tax, carbon emissions, and female economic inclusion. The population of the study comprises all countries that have data available on these variables between the period of 1994 to 2020. While there are limitations to this study, including the need for further research to fully understand the complex relationship between environmental taxation, carbon emissions, and female economic inclusion, this research represents an important contribution to the literature on these critical issues.
Keywords: 650; carbon emission; environmental pollution; Environmental tax; female inclusion; generalized method of moments